SISTEM KONTROL MOTOR 3 FASA MESIN POMPA AIR PADA PABRIK ES BALOK DENGAN MENGUNAKAN MODUL PLC OMRON TYPE CP1E - Sonny Rumalutur; Alimuddin Mappa; Jean Carlo Tarami (Electro Luceat, 2020)
This study discusses how to design a programmable logic controller (PLC) simulator trainer that can work and simplify human work and fast production. The 3-phase motor control of the water pump machine in the block ice cube is used with the CP1E-N20DR-D Omron PLC with a ladder diagram program designed with the Cx-Programmer computer application, as well as the design of communication media between the machine and the operator using the Cx-Designer software. As for the input / output used, the input is in the form of a level sensor module, the level sensor functions as a liquid barrier 1 and 2. The output is in the form of water pumps 1 and 2, the AC motor functions as filling and forming block ice and moving the ice cubes. Based on the research results, the Trainer Module for this ice block molding simulator is composed of several components that describe the process of making ice cubes by using the appropriate input / output and can work in accordance with the prearranged job descriptions.